PENERAPAN TEORI HIMPUNAN FUZZY PADA METODE PENGAMBILAN KEPUTUSAN SHYI-MING CHEN DAN RAMESH JAIN - TOHA
In a decision making we often face inaccurate data or information. Therefore, it requires a precise analysis to solve these kinds of problems. In this respect fuzzy set theory is used as a method to solve the problems. The fuzzy set theory is capable of giving a solution to an uncertainty; i.e the uncertainty based on vague limits, inaccurate information and ambiguity. Moreover, the fuzzy set theory was develoved from the idea that the key elements of human way of thinking were not based on ordinal value but on term or label. Decision making method using the fuzzy set theory proposed by Ramesh Jain accentuated the knowledge of a fuzzy situation or a fuzzy utility value. However the method is merely conceptual and therefore requires another method, which is more applicable to solve the problems of real decisions. Whereas another decision making method using the fuzzy set theory proposed by Shyi-Ming Chen gave more possibilities of aplicable i mplementations on real decision problems in the field. The final result of the decision which used the Ramesh Jain method following the Shyi-Ming Chen method will be better than the result of the decision which used those two methods separately.